2021
DOI: 10.3390/life11040285
|View full text |Cite
|
Sign up to set email alerts
|

Rice Transcriptome Analysis Reveals Nitrogen Starvation Modulates Differential Alternative Splicing and Transcript Usage in Various Metabolism-Related Genes

Abstract: Nitrogen (N) is crucial for plant growth and development; however, excessive use of N fertilizers cause many problems including environmental damage, degradation of soil fertility, and high cost to the farmers. Therefore, immediate implementation is required to develop N efficient crop varieties. Rice being low nitrogen use efficiency (NUE) and a high demand staple food across the world has become a favorite crop to study the NUE trait. In the current study, we used the publicly available transcriptome data ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…For example, nutrient stress caused differential AS regulation of the NRR gene in rice (Zhang Y. M. et al, 2012). Moreover, a recent study demonstrated that nitrogen starvation modulated differential AS and transcript usage of various metabolism-related genes in rice (Chaudhary and Kalkal, 2021), and AS of OsGS1;1 affects NUE, grain development, and amylose content in rice (Liu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, nutrient stress caused differential AS regulation of the NRR gene in rice (Zhang Y. M. et al, 2012). Moreover, a recent study demonstrated that nitrogen starvation modulated differential AS and transcript usage of various metabolism-related genes in rice (Chaudhary and Kalkal, 2021), and AS of OsGS1;1 affects NUE, grain development, and amylose content in rice (Liu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…RTD is the major backbone for accurate gene quantification of RNA-seq data analysis and consists of a list of genes and possible transcript isoforms of an organism ( Brown et al, 2017 ; Zhang et al, 2017a ; Rapazote-Flores et al, 2019 ; Vitoriano et al, 2021 ). The quality of the transcriptome annotation could help with fast and accurate estimation of transcript expression and AS events using the RNA-seq data with the help of the 3DRNA-seq tool ( Chaudhary and Kalkal, 2021 ; Guo et al, 2021 ; Vitoriano et al, 2021 ; Escudero-Martinez et al, 2022 ). Despite rice being an important crop plant and several attempts being made in the past to improve its transcriptome annotation and AS diversity, IndicaRTD contains a significantly higher number of transcript isoforms ( Lu et al, 2010 ; Zhang et al, 2010 ; Zhang H. et al, 2019 ; Schaarschmidt et al, 2020 ; Wang S. et al, 2022 ; Hasan et al, 2022 ; He et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chaudhary and Kalkal [1] present the results of bioinformatics analysis of publicly available transcriptome data generated from the root and shoot tissues of rice genotypes grown under optimal and nitrogen starvation conditions revealing the differentially expressed and alternatively spliced genes. This work extends our understating of nitrogen utilization efficiency mechanisms in the important crop plant.…”
mentioning
confidence: 99%